Women’s Empowerment through Self-Help Groups: A Case-Based Analysis from Rajasthan Aligned with the SDGs (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Transformation of lives of rural women towards their betterment is a critical issue in the development process of the countries around the world. Poverty, lack of financial awareness, minimal or no education and women disempowerment are reasons of poor condition of rural women. Globally, microfinance has become an integral part of poverty reduction, economic regeneration, and development. As part of India’s microfinance programs, Self Help Groups (SHGs) are utilised. The group consists of 10-20 voluntary members. These groups were formed from people who lived nearby and had mutual trust. Each member contributed a small amount to the corpus fund. SHG members could use those funds for livelihood activities or household needs. Numerous studies on the impact of SHGs reveal that SHG membership has led to economic, social, and political empowerment of rural women. SHGs have been actively used to promote livelihoods among rural women. The objective of this research paper is to analyse the role of Self-help groups in achieving the Sustainable Development Goals (SDGs). It presents case studies developed using a mixed methods approach, including literature review and qualitative data collected through focus group discussions and in-depth interviews with key informants and women SHG members in four districts of Rajasthan. Case study method has been chosen for this paper because it is regarded as a useful research method for exploring social phenomenon through multi-dimensional lenses. It helps in detailed analysis of a phenomenon in its real-life context. These women were from four districts across the 2 major geographical and agro-climatic regions of Rajasthan– Bikaner and Churu districts from northern region (irrigated through canals), Dungarpur and Sirohi from southern region (tribal dominated, rain-fed). The respondents belonged to different age groups of SHGs, namely, 0 to less than 1 year old, 1 to 3 years old, 3 to 5 years old, 5 to 8 years old, and more than 8 years old. The study concludes that SHGs have demonstrated some success in attaining various Sustainable Development Goals, such as SDG 1, SDG 2, SDG 5, SDG 8 and lastly SDG 10. Therefore, it’s important for the SHG program to be re-energized so that better access to financial service like availability of larger loans, trainings, and awareness programmes can be made available to women. It is utmost pertinent to ensure women’s nobility and security in all the policies and programmes on rural livelihoods.